2006
DOI: 10.1016/j.cub.2006.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Human Wapl Is a Cohesin-Binding Protein that Promotes Sister-Chromatid Resolution in Mitotic Prophase

Abstract: Wapl is a new regulator of sister chromatid resolution and promotes release of cohesin from chromosomes by directly interacting with its regulatory subunits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
459
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 405 publications
(491 citation statements)
references
References 34 publications
27
459
2
3
Order By: Relevance
“…Early studies had suggested that direct phosphorylation of cohesin subunits by Plk1 might promote release of cohesin from chromosome arms (Losada et al 2002;Sumara et al 2002). However, this process turned out to be much more complex, requiring a specialized releasing factor, Wapl (Gandhi et al 2006;Kueng et al 2006), and its partner, Pds5 (Shintomi and Hirano 2009).…”
Section: Prophase Condensation Mediated By Condensin II Coincides Witmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies had suggested that direct phosphorylation of cohesin subunits by Plk1 might promote release of cohesin from chromosome arms (Losada et al 2002;Sumara et al 2002). However, this process turned out to be much more complex, requiring a specialized releasing factor, Wapl (Gandhi et al 2006;Kueng et al 2006), and its partner, Pds5 (Shintomi and Hirano 2009).…”
Section: Prophase Condensation Mediated By Condensin II Coincides Witmentioning
confidence: 99%
“…The interaction of Wapl-Pds5 with the cohesin complex is multilayered and highly complex: Wapl, for instance, interacts not only with its regulatory subunits (SA1-Rad21/Scc1) (Gandhi et al 2006;Shintomi and Hirano 2009), but also with the SMC3 head domain (Chatterjee et al 2013). It will be of great interest and importance in the future to understand why HEAT repeats are found in many components of the cohesion and condensation machinery (Fig.…”
Section: Prophase Condensation Mediated By Condensin II Coincides Witmentioning
confidence: 99%
“…This reduced transmission is very sensitive to changes in the dosage of genes involved in chromosome segregation (Dobie et al 2001). For example, heterozygous wings-apart-like (wapl) mutations, which decrease mitotic chromatid separation by reducing prophase removal of cohesin from chromosome arms, decrease J21A transmission in female meiosis (Dobie et al 2001;Gandhi et al 2006;Kueng et al 2006;Verni et al 2000). Females heterozygous for the parental chromosome in which the Nipped-B 407 and Nipped-B 292.1 mutations were induced (Rollins et al 1999) transmitted J21A at a frequency of 0.24 (348 of 1,441; Table 2).…”
Section: Early Sc Breakdown In Nipped-b Mutants Does Not Affect Meiotmentioning
confidence: 99%
“…This population is essential in preventing precocious separation of the sister chromatids and allowing proper chromosome alignment (Vass et al 2003;Vagnarelli et al 2004;. The dissociation of cohesin in prophase requires Polo and Aurora B kinases as well as a number of additional factors that include Wapl Sumara et al 2002;Hauf et al 2005;Gandhi et al 2006;Kueng et al 2006). At the onset of anaphase, cleavage of Scc1/Rad21 by separase drives dissociation of the remaining cohesin and sister chromatid separation ensues (Hauf et al 2001).…”
Section: Introductionmentioning
confidence: 99%